ผลกระทบของสเวิร์ลนัมเบอร์ต่อคุณลักษณะการผสม ของเจ็ตร้อนที่หมุนควงในกระแสลมทวน - พงศ์พฤทธิ์ อุปถัมภ์นรากร (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Experiments for the investigation of the effect of swirl on the mixing characteristics of a heated swirling jet in counterflow were conducted. The heated swirling jet with non-zero tangential velocity, non-zero circulation was generated by passing hot air through a rotating pipe with honeycomb. Temperature distributions in the cross planes downstream of the jet were surveyed in order to investigate both local and global mixing characteristics. The experiments were conducted at a fixed effective velocity ratio of 4.62 and the swirl ratios (Sr) of 0 (no swirl), 0.11, 0.22, and 0.33, at a Reynolds number of approximately 10,000. The results were compared with those of the investigation of the effect of swirl on the mixing characteristics of a free swirling jet that were conducted in parallel. For free swirling jet, the results indicated that swirl enhanced jet mixing further from that of non-swirling jet. This was shown through increases in jet spreading and centerline temperature decay as swirl ratio was increased. On the other hand, swirl had little influence on the shape of average temperature distribution, both free swirling jet and non-swirling jet had symmetric, circular temperature distribution. For swirling jet in counterflow, the results indicated that swirl enhanced jet mixing even further from that of a jet in counterflow. This was shown through increases in jet spreading and centerline temperature decay and decrease in penetration depth as swirl ratio was increased. Similar to the free swirling jet case, swirl had little influence on the shape of average temperature distribution, being symmetric and circular as in the case of a jet in counterflow. When the effects of swirl on free swirling jet were compared to those on swirling jet in counterflow, they revealed that swirl had more influence on free swirling jet than swirling jet in counterflow. Specifically, the centerline temperature of free swirling jet decayed faster than that of swirling jet in counterflow, when comparison was made at the same amount of increase in swirl ratio. In particular, as swirl ratio increased from 0 (no swirl) to 0.33, the fifty-per-cent decay length, the length at which the excess temperature reduced to half of the original value at the jet exit (CT = 0.5), was shortened by 27% in swirling jet case and by 17% in swirling jet with counterflow case. In addition, the present study revealed that the effect of swirl on the penetration depth (xp) of a swirling jet in counterflow could be approximated by a parabolic relation: xp/d=-10.33Sr2-2.5Sr+12.63, where d was a diameter of the jet exit.